Pemberdayaan Perempuan Melalui Peningkatan Literasi Keuangan - Asrina, Putri; Yovita, Indri (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The role of women is crucial in the family. This is because women play many roles within the family. Women not only act as housewives but also play a role in helping the family economy and managing family finances. In managing family finances, it is crucial for women to have a good understanding of financial literacy. The purpose of this community service activity is to improve the financial literacy of women in Logas Village. This community service activity is carried out through lectures and training methods on the importance of financial literacy. This is done by providing information on the importance of financial literacy, financial management practices, and also discussing developments in financial digitalization. This activity targets women in Logas Village, Singingi District. This counseling activity is expected to help women who participate in the activity understand the importance of managing their finances and understand the principles of good financial management. Furthermore, the increasing ease of obtaining online loans, which results in poor financial management, will have an effect on dependence on loans, both direct and online. Therefore, counseling and financial literacy training are needed so that women in Logas Village, both married and single, can avoid unhealthy financial risks.